Application of supramolecular hydrogel in supercapacitors: Opportunities and challenges - Wenshi Xu; Aibing Chen (Aggregate)
Abstract Supercapacitors (SCs) are studied and used in various fields due to their high power density, fast charging/discharging rate, as well as long cycle life. Compared to other traditional electrode and electrolyte materials, supramolecular hydrogels have great advantages in the application of SCs due to their excellent properties. Unlike covalent bonds, supramolecular systems are assembled through dynamic reversible bonds, including host–guest interactions, ion interactions, electrostatic interactions, hydrogen bonding, coordination interactions, etc. The resulting supramolecular hydrogels show some special functions, such as stretching, compression, adhesion, self‐healing, stimulus responsiveness, etc., making them strong candidates for the next generation of energy storage devices. This paper reviews the representative progress of electrodes, electrolytes, and SCs based on supramolecular hydrogels. Besides, the properties of supramolecular hydrogels, such as conductivity, extensibility, compressibility and elasticity, self‐healing, frost resistance, adhesion, and flexibility, are also reviewed to highlight the key role of excellent properties of hydrogel materials in SCs. In addition, this article also discusses the challenges faced by current technologies, hoping to continue promoting future research in this field.